Pengaruh Konflik Internal dan Iklim Organisasi terhadap Semangat Kerja Pegawai PT Envesal Putera Megatrading, Tbk. Cabang Medan - Muhammad Fauzan Azhmy (Universitas Harapan Medan, 2021)
The purpose of this study was to determine whether internal conflict and organizational climate affect morale (spirit at work) either partially or simultaneously. The population of this study is the population in this study is the total number of 1 (one) division in the company PT Envesal Putera Megatrading Tbk. Medan as many as 154 employees. The number of samples taken in the study was 77 people using the random sampling method. The analysis technique used is multiple linear regression. The results of this study indicate that internal conflict and organizational climate have a significant effect both simultaneously and partially on employee morale.